2009
DOI: 10.3899/jrheum.090167
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Expression Profiles of Bone Morphogenetic Proteins, Tumor Necrosis Factor-superfamily Molecules, and Transcription Factor Runx2 Could Be Used as Markers of the Form of Arthritis, Disease Activity, and Therapeutic Responsiveness

Abstract: Our study identified BMP and Runx2 as possible biomarkers of bone metabolism in several forms of arthritis, while lower FasL and LIGHT were associated with RA. Correlation between gene expression and disease activity may be clinically useful in assessing therapeutic effectiveness and disease monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 55 publications
3
50
0
9
Order By: Relevance
“…Haroon et al used whole genome expression arrays to identify a response to anti-TNF treatment. 143 A subset of 1428 genes was differentially expressed in response to treatment and downregulation of 4 inflammation-associated genes, including LIGHT, whose downregulation has also been associated with RA suggesting this gene maybe generally associated with inflammatory processes, 144 was confirmed. Only recently however have large-scale whole genome expression profiling studies on the complete PBMC population been undertaken in AS or SpA by ourselves 145 and David Yu's group at UCLA.…”
Section: Circulating Cell Studiesmentioning
confidence: 89%
“…Haroon et al used whole genome expression arrays to identify a response to anti-TNF treatment. 143 A subset of 1428 genes was differentially expressed in response to treatment and downregulation of 4 inflammation-associated genes, including LIGHT, whose downregulation has also been associated with RA suggesting this gene maybe generally associated with inflammatory processes, 144 was confirmed. Only recently however have large-scale whole genome expression profiling studies on the complete PBMC population been undertaken in AS or SpA by ourselves 145 and David Yu's group at UCLA.…”
Section: Circulating Cell Studiesmentioning
confidence: 89%
“…As a major cell type responsible for bone reabsorption, OCs are formed in the mononuclear macrophage system and directly involved in the bone reformation (Eeles et al, 2015). Cellular research suggested that tartrate resistant acid phosphatase (TRAP) staining showed a positive response only after the differentiation and maturation of OC (Grcevic et al, 2010;Won et al, 2012). Other studies in AS-related hyperplasia also demonstrated the existence of large amounts of TRAP-positive mono-or poly-nuclear cells adhesive in the synovial tissue near the disease site, whereas no TRAP signal could be detected in cells near normal synovial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies it was demonstrated that anti-TNF alpha treatment leads to significant alteration of gene expression and protein profiles, supporting the use of systematic gene expression and proteomic analysis to shed new light on pathogenic pathways with importance in the chronic inflammation of AS (Haroon et al, 2010;Grcevic et al, 2010). Anti-TNF therapy induced a rapid change in the expression profile within 2 weeks in AS patients with down-regulation of lymphotoxins exhibiting inducible expression and competing with herpes simplex virus glycoprotein D for herpesvirus entry mediator, a receptor expressed by T lymphocytes (LIGHT), interferon receptor 1 (IFNAR1), interleukin 17 receptor (IL17R) and erythropoietin receptor (EPOR) genes.…”
Section: Gene Expression Changes After Anti-tnfα Therapymentioning
confidence: 99%
“…Although these results are interesting more studies are needed for validation. Another study using peripheral blood expression profiles based on PBMCs cells assessed several bone-regulatory factors as potential discriminators of different forms of arthritis, disease activity and therapy responsiveness (Grcevic et al, 2010). ROC curve analysis suggested higher expression of Runx2 was a potential molecular marker for AS.…”
Section: Gene Expression Changes After Anti-tnfα Therapymentioning
confidence: 99%